2015
DOI: 10.1002/ardp.201500238
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐Hepatitis B Virus Evaluation of 7‐Methoxy‐3‐heterocyclic quinolin‐6‐ols

Abstract: A series of novel 7-methoxy-3-heterocyclic quinolin-6-ol derivatives were synthesized and evaluated for their anti-hepatitis B virus (HBV) activities and cytotoxicities in the HepG2.2.15 cell line. Five compounds, 14a, 15c, 15e, 16b, and 16f, displayed excellent potency and selectivity toward the HBV, with IC values of less than 5.0 µM and selectivity index values of 11.0-71.5. Structure-activity relationship studies indicated that the 1,3,4-thiadiazole and sulfinylmethyl derivatives showed the most potent act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this context, Liu Y et al reported new series of thiadiazole derivatives 27, 28 and evaluated them for in vitro anti-HBV assay. They concluded that substitution of methyl group at 5th position and replacement of sulfide group with sulfinyl group increase the inhibition of DNA (HBV) [53]. In 2018, a novel chiral 1,3,4-thiadiazole based bis-arylsulfonamides was synthesized and evaluated for the treatment of HIV-1 and HIV-2 by Shafique M et al They found that compound 29 could be considered a new lead for the treatment of HIV as it displayed significant inhibitory activity against HIV-1 [54] (Figure 5).…”
Section: Treatment Of Hepatitis B Virus (Hbv) and Human Immunodeficie...mentioning
confidence: 99%
“…In this context, Liu Y et al reported new series of thiadiazole derivatives 27, 28 and evaluated them for in vitro anti-HBV assay. They concluded that substitution of methyl group at 5th position and replacement of sulfide group with sulfinyl group increase the inhibition of DNA (HBV) [53]. In 2018, a novel chiral 1,3,4-thiadiazole based bis-arylsulfonamides was synthesized and evaluated for the treatment of HIV-1 and HIV-2 by Shafique M et al They found that compound 29 could be considered a new lead for the treatment of HIV as it displayed significant inhibitory activity against HIV-1 [54] (Figure 5).…”
Section: Treatment Of Hepatitis B Virus (Hbv) and Human Immunodeficie...mentioning
confidence: 99%
“…Further acetyl group at C-5 of thiadiazole moiety presented noticeable increase in the activity rather than ethoxycarbonyl group. Liu et al (2015) have synthesized a series of 7-methoxy-3-heterocyclic quinolin-6-ol derivatives of the type 110a-e by incorporating 1,3,4-oxadiazole/1,3,4-thiadi azole nucleus in the heterocyclic moiety (Scheme 17) and were evaluated for their anti-Hepatitis B Virus (anti-HBV activities and cytotoxicities in HepG2.2.15 cell lines. It has been observed that compounds 109a, 110a, 110d, and 110e were found to be more potent and selective toward the HBV with IC 50 value less than 5.0 M and selectivity index values of 11.0-71.5.…”
Section: Hepatitis Virusesmentioning
confidence: 99%